The antibacterial activity and mechanism of a novel peptide MR-22 against multidrug-resistant Escherichia coli - Tian, Chunren; Zhao, Na; Yang, Longbing; Lin, Fei; Cai, Ruxia; Zhang, Yong; Peng, Jian; Guo, Guo (Frontiers in Cellular and Infection Microbiology, 2024)
Bacterial infections have become serious threats to human health, and the excessive use of antibiotics has led to the emergence of multidrug-resistant (MDR) bacteria. E. coli is a human bacterial pathogen, which can cause severe infectious. Antimicrobial peptides are considered the most promising alternative to traditional antibiotics. In this study, MR-22 is a new antimicrobial peptide with good activity that has demonstrated against MDR E. coli. The antimicrobial activity of MR-22 exhibited stability under conditions of high temperature, 10% FBS, and Ca2+. However, a decline of the activity was observed in the presence of Na+, serum, and trypsin. MR-22 had no significant cytotoxicity or hemolysis in vitro. SEM and fluorescent images revealed that MR-22 could disrupt the integrity of cell membrane. DCFH-DA indicated that MR-22 increased the content of reactive oxygen species, while it decreased the content of intracellular ATP. In mice model of peritonitis, MR-22 exhibited potent antibacterial activity in vivo. These results indicated that MR-22 is a potential drug candidate against drug-resistant E. coli.